Pengaruh Pembelajaran Berdiferensiasi dengan Model Flipped Classroom Berbantuan Platform s.id Terhadap Hasil Belajar Matematika Siswa - Sallyna, Sallyna; Rahmatina, Desi; Elvi, Mariyanti (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to determine the effect of differentiated learning with a flipped classroom model assisted by the S.id platform on students' mathematics learning outcomes. This research used a quantitative approach with a one-group pretest-posttest design. The population of this study comprised all seventh-grade students at SMP Negeri 1 Bintan. Purposive sampling technique was used based on the assessment of expert teachers, namely the seventh-grade mathematics teachers at SMP Negeri 1 Bintan. Data collection techniques used were tests and observations. The instruments used were the main instruments consisting of test sheets and observation sheets, as well as supporting instruments consisting of learning modules, differentiated learning materials, and question sheets. The data analyzed was quantitative data using the Paired-Sample T-test. The results showed that the average pretest and posttest scores were 43.1 and 76.2, respectively, with a significance value (2-tailed) of 0.000. The results revealed a significant difference between the pretest and posttest scores, indicating the effectiveness of differentiated learning with a flipped classroom model assisted by the s.id platform on students' mathematics learning outcomes. This, it can be concluded that there is an effect of differentiated learning with a flipped classroom model assisted by the S.id platform on students' mathematics learning outcomes.